CFD STUDY ON EFFECTS OF DIFFERENT WINDOW FILMS ON THE COOLING RATE OF ACADEMIC BUILDINGS IN UNIVERSITY TECHNOLOGY PETRONAS (UTP) - SHUKRI, FADHIL AIZAD (IRC, 2018)
In any building, window plays an important role for the building’s cooling system. Good positioning and the right amount of window in a specific building will provide the building a good cooling system. In today’s modern era, the evolution of normal window has taken place. These days, window films are present as a thin layer that can be installed in the interior or exterior part of the window to allow a specific amount of light and heat to go through it, depending on the film’s specifications. Based on pass research, with the installation of window films, the cooling of the building will be more effective with little use of air conditioning power resulting in saving of energy in buildings. In this project, a research will be done on how different types of window films can affect the rate of cooling of the academic buildings in University Technology Petronas (UTP). This project is done by performing simulations using the ANSYS Fluent 18.2 software to observe and analyze on how different window films with different specifications shows the results of the simulations. The window films that were used in this simulation are UTP’s default window films, low emissivity DGU window film, solar control DGU window film and clear float DGU type window film. The U-factor and SGHC value of these window films act as the main manipulating factor for this simulation. The simulated room used in this simulation will be UTP’s academic block 17-03-25 with the air conditioning running at constant velocity. Completing all simulations, it is concluded that the lower U-factor and SGHC value of the windows give better cooling rate for the simulated room. At the end of this project, after done studying and analyzing the data, the most suitable type of window films that should be used in UTP’s academic building can be suggested.